Bangladesh : 2007 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2007 Article IV Consultation on Bangladesh highlights recent developments and policy discussions. Bangladesh's growth outlook and external position remain robust, but inflation has picked up. Overall macroeconomic stability has been maintained, but fiscal performance continues to suffer from structural weaknesses. Executive Directors welcomed the planned reforms in the area of public financial management and the adoption by major ministries of the medium-term budget framework. They supported the recent reforms to promote transparency, fair elections, and the prevention of money laundering.